1990
DOI: 10.1002/crat.2170251102
|View full text |Cite
|
Sign up to set email alerts
|

“Crystallization E.M.F.” Investigation in the lithium niobate pulling process from the melt

Abstract: . in the lithium niobate crystal-melt system as a function of pulling and rotation rates, crystal diameter and orientation was determined. Total E.M.F. is a sum of thermo-E.M.F. and "crystallizationwhere u is a growth rate, dq, = 3.9 mV, u,, = 1.9 mm/h is adequate. The A q magnitude is independent within the experimental error on the rotation rate and crystal orientation, whereas it is slightly increasing along with the diameter increase. Some existing models of electric phenomena accompanying crystal growth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…The Df-DT curve was similar to the ones reported in Ref. [6] and [12]. In our Df-DT curve, a deflection was observed in the solid phase at around DT ¼ 170 K. This was attributed to the sudden change in the growth rate.…”
Section: Article In Presssupporting
confidence: 88%
See 2 more Smart Citations
“…The Df-DT curve was similar to the ones reported in Ref. [6] and [12]. In our Df-DT curve, a deflection was observed in the solid phase at around DT ¼ 170 K. This was attributed to the sudden change in the growth rate.…”
Section: Article In Presssupporting
confidence: 88%
“…In their reports, even though D'yakov et al [6] and Aleksandrovskii and Shumov [12] reported similar measurements using a Czochralski method, the mechanism of crystallization EMF was not elucidated. D'yakov et al [6] considered the crystallization EMF, Df EMF , to be linearly proportional to the growth rate and represented it in the form Df EMF ¼ a V V, where a V and V represent a linear constant and the growth rate, respectively.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…D'yakov et al [1] and Aleksandrovoskii et al [2] demonstrated the intrinsic electric potential distribution occurring around the solid-liquid interface, which consists of thermoelectric power (Seebeck effect) and electromotive force (EMF) during the growth of congruent LiNbO 3 by the Czochralski method. Uda and Tiller [3] discussed that EMF is associated with a charge separation effect resulting from the net charge by all existing ions in the melt which has a simple relationship with the growth velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we must differentiate the partitioning of ionic species from that of bulk components. Segregation of ionic species at the congruent composition was experimentally observed during growth of LN crystal using the Czochralski method by measuring the crystallization EMF generated near the growth interface [10,11].…”
Section: Introductionmentioning
confidence: 99%